Analisa Harga Pokok Penjualan dalam Menentukan Laba pada Rumah Makan Putri Solo “Takana Jo Kampuang” Muara Bulian - Muryati Muryati; Joko Susilo (Universitas Batanghari Jambi, 2021)
This study aims to analyze the calculation of the cost of sales as the basis for determining the selling price of the product in determining profit in one period at The Putri Solo Restaurant